FGF21 Regulates Sweet and Alcohol Preference - Talukdar, Saswata (Cell Metab, 2015)
Fibroblast growth factor 21 (FGF21) is a hormone induced by various metabolic stresses, including ketogenic and high carbohydrate diets, that regulates energy homeostasis. In humans, SNPs in and around the FGF21 gene have been associated with macronutrient preference, including carbohydrate, fat and protein intake. Here we show that FGF21 administration markedly reduces sweet and alcohol preference in mice, and sweet preference in cynomolgus monkeys. In mice, these effects require the FGF21 co-receptor β-Klotho in the central nervous system and correlate with reductions in dopamine concentrations in the nucleus accumbens. Since analogs of FGF21 are currently undergoing clinical evaluation for the treatment of obesity and type 2 diabetes, our findings raise the possibility that FGF21 administration could affect nutrient preference and other reward behaviors in humans.